PERSEPSI MAHASISWA TERHADAP PROFESI AKUNTAN DAN DAMPAKNYA PADA PROGRAM STUDI AKUNTANSI - Ietje Nazaruddin (Journal of Accounting and Investment, 2008)
Recently many accounting programs have simultaneously faced declining enrollments.  Changes in business environment have created a perceived need more creative individuals in the accounting profession.  This study asserts that to attract these people, we will have to change existing perceptions of the profession.  The present study focuses on the point by examining the relationship between students’ inherent creativity, their perceptions of the accounting profession and their decisions to choose accounting as major.  Finding indicate that a student view of the accounting profession as interesting relates negatively to interaction between the student’s inherent creativity and the extent to which he or she holds a traditional view of accounting.